Mechanisms of action and resistance prevention of synergistic thymol and carvacrol combinations with antibiotics in Staphylococcus aureus and Acinetobacter baumannii - Cristina Gan; Elisa Langa; Gang Wang; Françoise Van Bambeke; Diego Ballestero; María Rosa Pino-Otín (Natural Products and Bioprospecting)
Abstract The use of natural products as antibiotic adjuvants to enhance efficacy and mitigate resistance is increasingly recognized as a promising strategy. This study explored five novel synergistic antimicrobial combinations (SACs) of carvacrol (CARV) and three already identified SACs of thymol (THY) with chloramphenicol, gentamicin, and streptomycin against Staphylococcus aureus and Acinetobacter baumannii, critical WHO-listed pathogens, and investigated their mechanisms of action and resistance-prevention capabilities. Despite being isomers, CARV and THY exhibited distinct synergistic effects and fractional inhibitory concentration index (FICI) values depending on the antibiotic and bacterial species. The SACs significantly reduced the required antibiotic dose by 4- to 16-fold, with FICI values ranging from 0.25 to 0.5. Growth kinetics revealed that SACs completely inhibited planktonic bacterial growth, outperforming antibiotics alone. Additionally, the SACs demonstrated efficacy in both inhibiting and eradicating biofilms of S. aureus and A. baumannii. Resistance development studies highlighted that neither THY nor CARV induced resistance in these pathogens. Moreover, SACs combining aminoglycosides with THY reduced the emergence of resistance in A. baumannii by up to 32-fold. In S. aureus, THY mitigated gentamicin resistance by 16-fold. CARV exhibited similar, albeit slightly less potent, effects. Mechanistic investigations revealed that THY and CARV exert antimicrobial action by multiple mechanisms, including bacterial membrane depolarization and disruption, efflux pump inhibition, disrupting ATP metabolism and mitigating oxidative stress induced by antibiotics. These findings highlight the potential of SACs to enhance antibiotic efficacy while preventing resistance, positioning them as strong candidates for innovative antimicrobial therapies against multidrug-resistant pathogens. Graphical Abstract